The memo : five rules for your economic liberation - Bryant, John, 1966- (BK life book., 2017)
True power in this world comes from economic independence, but too many people have too much month left at the end of their money. John Hope Bryant, founder and CEO of Operation HOPE, illuminates the path toward liberation that is hiding in plain sight. His message is simple: the supermajority of people who live in poverty, whom Bryant calls the invisible class, as well as millions in the struggling middle class, haven't gotten "the memo"--Until now. Building on his personal experience of rising up from economically disadvantaged circumstances and his work with Operation HOPE, Bryant teaches readers five rules that lay the foundation for achieving financial freedom. He emphasizes the inseparable connection between "inner capital" (mindset, relationships, knowledge, and spirit) and "outer capital" (financial wealth and property). "If you have inner capital," Bryant writes, "you can never be truly poor. If you lack inner capital, all the money in the world cannot set you free." Bryant gives readers tools for empowerment by covering everything from achieving basic financial literacy to investing in positive relationships and approaching wealth with a completely new attitude. He makes this bold and controversial claim: "Once you have satisfied your basic sustenance needs--food, water, health, and a roof over your head--poverty has more to do with your head than your wallet." Bryant wants to restore readers' "silver rights," giving them the ability to succeed and prosper no matter what very real roadblocks society puts in their way. We have more power than we realize, if only we can recognize and claim it. "We are our first capital," Bryant writes. "We are the CEOs of our own lives."